Suppression of tumor-associated neutrophils by lorlatinib attenuates pancreatic cancer growth and improves treatment with immune checkpoint blockade - Nielsen, Sebastian R.; Strøbech, Jan E.; Horton, Edward R.; Jackstadt, Rene; Laitala, Anu; Bravo, Marina C.; Maltese, Giorgia; Jensen, Adina R. D.; Reuten, Raphael; Rafaeva, Maria; Karim, Saadia A.; Hwang, Chang-Il; et al. (Nature communications, 2021)
Pancreatic ductal adenocarcinoma (PDAC) patients have a 5-year survival rate of only 8% largely due to late diagnosis and insufficient therapeutic options. Neutrophils are among the most abundant immune cell type within the PDAC tumor microenvironment (TME), and are associated with a poor clinical prognosis. However, despite recent advances in understanding neutrophil biology in cancer, therapies targeting tumor-associated neutrophils are lacking. Here, we demonstrate, using pre-clinical mouse models of PDAC, that lorlatinib attenuates PDAC progression by suppressing neutrophil development and mobilization, and by modulating tumor-promoting neutrophil functions within the TME. When combined, lorlatinib also improves the response to anti-PD-1 blockade resulting in more activated CD8 + T cells in PDAC tumors. In summary, this study identifies an effect of lorlatinib in modulating tumor-associated neutrophils, and demonstrates the potential of lorlatinib to treat PDAC. Tumor associated neutrophils have been correlated with poor prognosis in patients with pancreatic ductal adenocarcinoma (PDAC). Here the authors show that the tyrosine kinase inhibitor lorlatinib modulates neutrophil development and recruitment in the tumor microenvironment, attenuating PDAC progression in preclinical mouse models.